Hydro-Oceano & Sedimentation Model of Brondong Lamongan Harbour - Thufail Basyarahil Moch; Abdi Perdanawati Rizqi; Fahmi M. Yunan (BIO Web of Conferences, 2025)
PPN Brondong in East Java is a vital fisheries hub, catching around 200 tonnes of fish in a day and serving as an export hub. To maintain port efficiency and properly manage vessel activities, hydro-oceanographic modelling is important. This research uses a quantitative approach with primary and secondary data analysis. Using Delft3D, this study modelled the currents and sedimentation in PPN Brondong for one year, covering the east and west monsoons. The results show a diurnal tidal pattern, with dominant winds from the east in the east monsoon and west in the west monsoon. Peak waves reached 1.6 metres in the west monsoon and 0.9 metres in the east monsoon. The maximum current velocity of 0.23 m/s occurred in the west monsoon. TSS was higher in the west monsoon, reaching 1kg/m3. Erosion and sedimentation differed between monsoons; steady erosion occurred in shallow areas and sedimentation in deeper areas. The eastern harbour basin is prone to erosion due to high currents, while the western part experiences sedimentation. This research provides in depth understanding for sustainable harbour management at PPN Brondong.